Assessing higher education students’ critical thinking with the PENCRISAL test - Portuguese short version: a psychometric study - Rivas, Silvia F.; Franco, Amanda; Vieira, Rui Marques; Almeida, Leandro S.; Saiz, Carlos (Frontiers in Psychology, 2023)
The development of critical thinking in higher education is fundamental, preparing students to think well, find explanations, make decisions and solve problems. Given the importance of its promotion, its assessment is crucial, since the two are inseparable. Moreover, the number of instruments that are validated to assess critical thinking in the Portuguese language and culture do not abound. We present the validation psychometric study of the PENCRISAL test (short version) to the Portuguese language, a critical thinking assessment test for higher education students, designed and validated in Spain, which presents psychometric characteristics that make it a reliable, valid, and ecological instrument to assess key-dimensions of critical thinking. This version presents consistent indexes in the factor analysis, and moderately robust coefficients regarding reliability and validity, which support this structure. Here, assessment is at the service of promotion, offering an instrument that supports the development of critical thinking in higher education.